COMPRESSIVE STRENGTH OF CONCRETE USING PLASTIC BOTTLE WASTE AGREGAT ADDED AS MATERIAL ROUGH - Nandy Candra; Whendy Trissan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2021)
Plastic bottle is waste that can be utilized. This research is used as additive in concrete mixtures can provide an alternative to Utilize the waste. Such as waste plastic bottles PET (Polyethylene Terephthalate). Optimizing the utilization of waste plastic bottles PET (Polyethylene Terephthalate) is expected to reduce the waste that pollutes the environment and provide added value.The fiber to be used as an additive in concrete mixtures. The fibers are mixed with fine aggregate, water and PPC cement type I gresik brands. Concrete mix design using SNI 03-2843-2000 about how making plans mixture of normal concrete. Tests using a cylinder measuring 10 cm x 20 cm, each variation using 10 samples consisting of five variations (0%, 5%, 10%, 15%, 20%) and tested at 14 and 28 days in Laboratory Studies Engineering Education building the Faculty of Education University of Palangkaraya.Average compressive strength at 14 days for variations of coarse aggregate mixture of chopped plastic bottle 0%, 5%, 10%, 15% and 20%, respectively for 23:02 MPa; 12:35 MPa; 10.49 MPa; 9.6 MPa; 8.83 MPa. Average compressive strength at 28 days for variations of coarse aggregate mixture of chopped plastic bottle 0%, 5%, 10%, 15% and 20%, respectively for 25.77 MPa; 13.62 MPa; 11.84 MPa; 10.8 MPa; 10:28 MPa